Molecular Determinants of Radiation Response - DeWeese, Theodore L.; Laiho, Marikki; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2011)
The DNA of mammalian cells is constantly under assault from both endogenous and exogenous sources.  Ionizing radiation is one of the most important sources of genomic injury because of its ability to inflict substantial cellular damage that is both therapeutic as well as mutagenic.  Mammalian cells have evolved an impressive array of DNA damage response mechanisms that are called upon to respond to and repair radiation-induced DNA injury that allow cells to survive with DNA fidelity intact.  Contemporary oncologic research and patient management demand a thorough understanding of these DNA damage response processes as well as some of the important environmental conditions like hypoxia in which cells exist such that strategies that subvert these survival processes can be considered and exploited for therapeutic gain. Molecular Determinants of Radiation Response includes chapters by expert authors who detail the present understanding of key DNA damage response pathways and proteins.  The chapters include comprehensive discussions on where and how specific alterations in function of these pathways and proteins result in substantive modifications of cellular response to DNA injury.   The authors have done a wonderful job in providing meaningful reviews, with appropriate detail and scope for both the well informed reader as well as the novice looking for new information.  Given the importance of therapies that induce DNA injury in the management of human disease, this book is timely and relevant for basic and translational researchers, as well as clinicians alike.
Molecular Basis of the DNA Damage Responses -- ATM signaling and DNA Damage -- H2AX in DNA Damage Response -- Dynamic Imaging of DNA Damage Foci -- DNA Damage Signaling Downstream of ATM -- Checkpoint Control and Radiation -- Chromatin Responses to DNA Damage.-DNA Damage Response and Senescence -- C. elegans and DNA Damage -- Modulation of Radiation Responses – Opportunities for Therapeutic Exploitation -- The Stem Cell and Radiation -- Role of the Cell Membrane in Signaling Radiation Injury -- Hypoxia and Modulation of Cellular Radiation Response -- Role of PARP and PARP Inhibition in Cellular Response to Radiation -- Anti-angiogenic Therapies and Radiation Responses -- Gene Therapy and Radiation -- Radiation-mediated Molecular Targeting -- EGFR Signaling and Radiation -- Heat and Heat Shock Proteins Modulation of Radiation Response -- Radiation-induced Immune Modulation.
Keywords: Cancer research; Pharmacology; Cancer Research; Pharmacology/Toxicology.